Fabrication and Path Following Control of a Magnetic Soft Microrobot - Tang, Jianhui; Zhang, Pan; Wu, Jundong; Wang, Yawu (2022 8th International Conference on Control Science and Systems Engineering (ICCSSE), 2022)
Magnetically-controlled soft microrobots have great application prospects because of small size, flexible motion and wireless control. In this paper, a magnetically-controlled soft microrobot is designed and fabricated. In order to achieve its path-following control, two open-loop control strategies and a closed-loop one are developed. Especially, for the closed-loop control strategy, we present the image processing method and the pure pursuit algorithm, where the former is used to obtain the position and posture of the microrobot required for the latter. Finally, the developed open-loop and closed-loop control strategies are verified by carrying out the experiments. These methods are promising in numerous applications because of the ease of implementation.